Dinâmica da serapilheira em fragmento de Floresta Atlântica, ES - Gomes Júnior, Diêgo (2017)
The dynamics of litter is one of the fundamental processes for the growth and maintenance of native forest fragments, being considered the main route of the cycling of nutrients in forests. Thus, works that report the production, accumulation and litter decomposition, provide subsidies that supply a better understanding of nutrient dynamics. The aim of this work was to know the litter and nutrients dynamics, by litter deposition, accumulation and decomposition, in a fragment of Atlantic Forest in the south of the state of Espírito Santo. In order to do so, the soil study was carried out by opening three representative soil profiles previously established, observing the relief and pedological characteristics. The profiles were opened in the lowland, in the middle third of hillside and at the top of the hill, being morphologically described with subsequent analysis of the physical and chemical properties. The litter sampling was carried out monthly in 12 permanent plots, from April/2014 to March/2015 (year 1) and from April/2015 to March/2016 (year 2). The litterfall was collected using five fixed traps and the litter of the forest floor was collected by eight random samplings. The litterfall was sorted into leaves and branches + miscellaneous fractions, and the biomass and nutrients were quantified, this procedure also was performed for accumulated litter. The decomposition rate of the accumulated litter was obtained by the relation between production and accumulation of litter. The foliar decomposition rate was obtained using the litterbags method, by the distribution of 72 litterbags in the 12 plots (6/plot), one litterbag/plot was collected at 0, 30, 60, 90, 150, 210 and 270 days. The evaluated profiles have soils texture varying from sandy to very clayey, with pH values in water varying from 3.33 to 6.07. The cation exchange values varied from 1.23 to 13.99 cmolc dm-3, with predominance of Ca2+ in the lowland and slope soils, and H+ in the top of hill soil. Lowland and slope soils are eutrophic, while the top of hill soil is dystrophic. The N-total and Corg stocks were higher top of hill soil (22.05 and 173.05 Mg ha-1), followed by slope soil (18.24 and 112.27 Mg ha-1) and lowland soil (16.87 and 85.61 Mg ha-1). By observing characteristics, the soil profiles were classified as Planossolo in the lowland, Cambissolo in the hillside and Latossolo in the top of hill. The litterfall showed a seasonal pattern in the two years studied, producing 7826.6 and 5741.4 kg ha-1 year- 1, in years 1 and 2, respectively. The accumulated litter did not show seasonality, accumulating 5458.6 and 5079.4 kg ha-1 year-1 for year 1 and 2, respectively. The order of the nutrients content of the litterfall was Ca > N > K > Mg > S > P, for the two years of study. The decomposition constant of the accumulated litter was 1.43 and 1.13 for year 1 and 2, respectively. The leaf litter decomposition rate was 0.90, decomposing 58.28% of the litter at the end of the evaluated period. The leaf litter liberated 48% of N, 66% of P, 90% of K, 37% of Ca, 66% of Mg, 51% of S and 80% of Corg of the total contained. The precipitation was the climatic element that had the greatest correlation with the litter production, accumulation and decomposition, demonstrating that the litter dynamics is conditioned by the variation of rainfall indices.